Stevens’ Cure (Umckaloabo)—the vindication of a patent medicine - Brendler, T.; Stander, M. A.; van Wyk, B.-E. (Frontiers in Pharmacology, 2024)
Stevens' Cure (Umckaloabo) emerged as a patent medicine claiming to treat tuberculosis in the United Kingdom at the beginning of the 20 th century. However, due to its identity being shrouded by secrecy, it was never truly accepted by the medical community. It was "rediscovered" in the 1970s and subsequently developed into a very popular and successful phytopharmaceutical for the treatment of upper respiratory tract infections. Whether Stevens' Cure contained the same ingredient(s) as the modern Umckaloabo has not yet been demonstrated. We attempted to elucidate for the first time the identity of the original ingredient by comparative analysis of historical product samples. Three historical samples of Stevens' Cure were compared with Pelargonium sidoides DC. and P. reniforme Curt. root per UPLC-MS analysis. We confirm that the ingredient -P. sidoides DC.is indeed the same as used in modern phytotherapy. We also attribute the first ethnopharmacological record of P. sidoides DC. being used for the treatment of tuberculosis to C. H. Stevens, the "creator" of Umckaloabo.